LOX-1 Deletion Attenuates Myocardial Fibrosis in the Aged Mice, Particularly Those With Hypertension - Li, Xiao; Tang, Xihe; Liu, Bo; Zhang, Jinghang; Zhang, Yongxi; Lv, Hefan; Liu, Dongling; Mehta, Jawahar L.; Wang, Xianwei (Frontiers in Cardiovascular Medicine, 2021)
Background: Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is a transmembrane glycoprotein that mediates uptake of oxidized low-density lipoprotein (ox-LDL) into cells. Previous studies had shown that LOX-1 deletion had a potential to inhibit cardiac fibrosis in mouse models of hypertension and myocardial infarction. Whether LOX-1 deletion also affects cardiac fibrosis associated with aging still remains unknown. The aim of this study was to investigate the effect of LOX-1 deletion on myocardial fibrosis in the aged mice. Methods: C57BL/6 mice and LOX-1 knockout (KO) mice with C57BL/6 background were studied to the age of 60 weeks. Both genotypes of aged mice were exposed to angiotensin II (Ang II) or saline for additional 4 weeks. The mice were then sacrificed, and myocardial fibrosis, reactive oxygen species (ROS) and expression of LOX-1, fibronectin, collagens, p22phox and gp91phox were measured. Results: LOX-1 deletion markedly reduced Ang II-mediated rise of blood pressure in the aged mice (vs. saline-treated mice). LOX-1 deletion also limited fibrosis and decreased fibronectin and collagen-3 expression in the hearts of aged mice, but not the expression of collagen-1 and collagen-4. LOX-1 deletion also inhibited ROS production and p22phox expression. As the aged mice were exposed to Ang II for 4 weeks ( resulting in hypertension), LOX-1 deletion more pronounced inhibiting myocardial fibrosis and ROS production, and decreasing expression of fibronectin, collagen-1, collagen-2, collagen-3, p22phox and gp91phox. Conclusion: LOX-1 deletion limited fibrosis and ROS production in the hearts of aged mice. This effect was more pronounced in the aged mice with hypertension induced by Ang II infusion.